Creating a Scottish church : Catholicism, gender and ethnicity in nineteenth-century Scotland - Kehoe, S. K. (Manchester University Press ; Distributed in the U.S. exclusively by Palgrave Macmillan, 2010)
Highlighting how the Catholic population participated in the extension of citizenship in Scotland, this book considers Catholicism's transition from an underground and isolated church into a multi-faceted institution.